Effect of temperature and cropping sequence on the infestation pattern of Bemisia tabaci in potato - SHAH, MOHD ABAS; MALIK, KAMLESH; BHATNAGAR, ANUJ; KATARE, SUBHASH; SHARMA, SANJEEV; CHAKRABARTI, SWARUP KUMAR (The Indian Journal of Agricultural Sciences, 2019)
In India, more than 85% of the total potato production is realised from the subtropical Indo-Gangetic plains where potato is cultivated during winter. The cotton whitefly, B. tabaci is a major pest of potato as it transmits the Tomato leaf curl New Delhi virus (potato) causing the Apical leaf curl disease which leads to huge yield losses. The population dynamics of cotton whitefly was studied at 12 locations across the northern plains of India from 2015–17. It was observed that the cotton whitefly appears on potato immediately after crop emergence. The whitefly adults exhibited four different patterns of population dynamics at different locations. Whiteflies remained on the potato crop as long as minimum daily temperature was above 10–12ºC after which the whiteflies either disappeared from the crops or their flight activity was considerably reduced as indicted by the yellow sticky trap catch data. The whitefly incidence was higher at locations where potato is preceded by crops preferred by whitefly such as cotton, broad beans, groundnut etc. Perusal of the data on number of eggs laid and ensuing nymphs per plant indicated that the contribution of immigrating adults to the whitefly population is much higher than that of the colonising population for major part of the crop period. Thus, in addition to temperature, cropping sequence acts as a major factor in shaping the pattern of whitefly infestation. The results will help in deciding cropping pattern and better timing of insecticidal applications for healthy seed potato production.